SELECTING READING MATERIALS FOR READING CLASS - Andriani, Desi (Menara Ilmu, 2018)
This article discusses about the ways how English teacher chooses reading texts for his/ her students. In selecting the texts, teacher pays attention to the words of the texts. The number of function and lexical words of the texts is considered in selecting texts. Function words are such as the, a, an, this, those, that and these. Lexical words are words that refer to someone, things, actions and properties.Key words: texts, function words, lexical words